ICT portal for the development of mathematic teachers competence: The development and the feasibility - Jefri Marzal; Wardi Syafmen; Husni Sabil (invotek, 2021)
One of the problems in improving the competence of Information and Communication Technology (ICT) for mathematics teachers is that the teacher has to leave his / her teaching activities to participate in various improving competence events. This study aims to develop an ICT house portal that will be managed by the Mathematics Subject Teacher Forum in Indonesia or known as MGMP that allows teachers to interact with fellow teacher communities to improve ICT competence without having to leave their teaching activities at school. Furthermore, the researchers also conducted a usability test of the developed portal. The application development model used is the ADDIE model which stands for Analysis, Design, Development, Implementation, Evaluation. Meanwhile, application usability testing was carried out by distributing usability questionnaires to 30 respondents consisting of postgraduate students and lecturers of mathematics education. The results showed that the ADDIE model can be used to design and create the ICT house portal called RumahTIK where the procedures in the development section include making applications, testing by experts, testing content filling, testing the use of clinical features. Based on the results of the usability questionnaire processing, the percentage of usability was 81% which was classified as very feasible. Although this research was not implemented for real teacher groups, the ICT house portal is very suitable for use by the MGMP group. In the future, it is necessary to implement this portal in various MGMP groups so that recommendations can be obtained to improve teachers' ICT competence in mathematics.